Revisiting Caveiro Lake sediment record: the Holocene NAO and AMO impact on Pico Island (Azores archipelago) - Giralt, Santiago; Hernández, Armand; Raposeiro, Pedro Miguel; Gonçalves, Victor S.; Pueyo Mur, Juan José; Trigo, R. M.; Bao, Roberto; Sáez, Alberto (2017)
Northern Hemisphere climate is partly conditioned by a number of atmospheric and oceanic patterns which occur in the North Atlantic sector. The favourable location of the Azores Archipelago (37°¿40° N, 25°¿31° W) results in a privileged place to generate high-resolution Holocene climatic proxy data that can contribute to deep our understanding on the evolution of these atmospheric and oceanic patterns. In the frame of three research projects, namely PALEONAO (CGL2010-15767), RAPIDNAO (CGL2013-40608-R) and PALEOMODES (CGL2016-75281-C2), high-resolution proxy-based reconstructions from Azores Archipelago have recently shown a combined impact of atmospheric and oceanic patterns at multiannual and decadal time-scales (Rubio-Inglés et al. 2016; Hernández et al. 2017). However, the long-term evolution coupling/uncoupling of these patterns is not well-determined yet. Here, we present a new high-resolution climate reconstruction based on the Caveiro Lake sedimentary sequence in order to fill this gap. Previously, Björck et al. (2006) studied a section of this sequence (the uppermost 4.6 m covering last 6 Ka cal BP) concluding that changes in the thermohaline circulation and the SST were the main drivers in the long-term precipitation variability, whereas the NAO impact was the main atmospheric driver of short-term precipitation changes. However, they only distinguished the NAO impact for the last 600 years owing to the low resolution of the study for the lower portion of the core. The new studied sequence (8.40 m long, 8.2 Ka cal BP) has been analysed at decadal-to centennial time-scale resolution for X-ray diffraction (XRD), X-ray fluorescence (XRF) core scanning and elemental and isotope geochemistry on bulk organic matter. The statistical multivariate analysis of the data highlights the main drivers triggering the sedimentary infill of the lake would be the NAO and AMO by controlling the lacustrine productivity via nutrients input. This new high-resolution climate reconstruction from Caveiro Lake disentangles the ...